Peak-type charge barriers enabling high surface-insulating performance of epoxy composites. (20th October 2022) - Luo, Zimin; Zhao, Yushun; Bai, Jinhui; Yang, Kerong; Xu, Yufan; Ding, Lijian; Du, Bin
Abstract: The rapid increase in electrical and electronic devices integration necessitates the urgent development of epoxy composites with more reliable surface-insulating performance. Charge traps with valley -like features are known to improve the surface-insulating characteristics of insulating materials. Inspired by this strategy, a new approach is reported herein for constructing peak -type charge barriers to enhance the surface-insulating performance of epoxy composites. This paper describes the construction of 0.92 eV peak-type charge barriers on the surface of an epoxy composite by doping with nanodiamonds (NDs), which have a negative electron affinity. The constructed barriers alter the charge migration behavior on the surface of the ND/epoxy composite. Consequently, the charge dissipation rate and surface flashover voltage of the ND/epoxy composite increase by 563% and 17.6%, respectively. Additionally, the NDs improve the arc resistance duration of the epoxy resin by 211%, owing to their electron-emitting effect under strong electrical fields. This strategy, by which the peak-type charge barriers constructed using the NDs exhibit excellent surface-insulating characteristics to the epoxy composites, can be adopted as a new approach to improve the surface-insulating abilities of materials. Graphical abstract: Innovative peak -type charge barriers constructed via nanodiamond (ND) doping promote the surface-insulating characteristics of epoxy composites. The peak-type charge barriers prevent charge migration on the surface of the material and inhibit charge accumulation, substantially improving its surface flashover performance. The low field-emission-threshold voltage of the NDs imparts an excellent arc resistance to the material. Image 1